Relative Sea-Level Changes and Ice Sheet History in Finderup Land, North Greenland - Strunk, Astrid; Larsen, Nicolaj K.; Nilsson, Andreas; Seidenkrantz, Marit-Solveig; Levy, Laura B.; Olsen, Jesper; Lauridsen, Torben L. (Frontiers in Earth Science, 2018)
Rising global sea level caused by melting ice sheets poses a major challenge in a persistently warming climate. The Greenland Ice Sheet (GrIS) is among the main contributors, and in order to make accurate predictions of future ice retreat and sea level rise, it is imperative to understand how the ice sheet responded to global warming in the past. Reconstructions of relative sea level (RSL) are a key constraint in models of past ice sheet fluctuations, however, high-precision data has until now been sparse in North Greenland. In this study, we present a RSL reconstruction for Finderup Land, North Greenland based on five isolation lakes located between 19.6 and 81.2 m a.s.l. The transition between marine and lacustrine sediments has been identified using XRF, lithological interpretation, and foraminiferal analysis. Age constraints are based on 14C dating of foraminifera and paleomagnetic age correlation. Our results show that Finderup Land was ice free by 10.8 ± 0.2 cal ka BP with a subsequent rapid RSL fall occurring from 9.5 ± 0.2 to 8.0 cal ka BP, at which point the RSL started to approach present level. Furthermore, we establish the marine limit to be minimum at 81.2 m a.s.l. We compare our data to modeled RSL predictions for the area and our results indicate a faster RSL fall, which in turn reflects that the ice retreat was more rapid than estimated and possibly, that the ice sheet in North and Northeast Greenland was larger than previous estimates suggest.